Avoiding Complications in Endoscopic Third Ventriculostomy - Yadav, Yad Ram; Parihar, Vijay Singh; Ratre, Shailendra; Kher, Yatin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Endoscopic neurosurgical techniques hold the potential for reducing morbidity. But they are also associated with limitations such as the initial learning curve, proximal blind spot, visual obscurity, difficulty in controlling bleeding, disorientation, and loss of stereoscopic image. Although some of the surgical techniques in neuroendoscopy and microsurgery are similar, endoscopy requires additional skills. A thorough understanding of endoscopic techniques and their limitations is required to get maximal benefit. Knowledge of possible complications and techniques to avoid such complications can improve results in endoscopic third ventriculostomy (ETV). The surgeon must be able to manage complications and have a second strategy such as a cerebrospinal fluid shunt if ETV fails. It is better to abandon the procedure if there is disorientation or a higher risk of complications such as bleeding or a thick and opaque floor without any clear visualization of anatomy. Attending live workshops, practice on models and simulators, simpler case selection in the initial learning curve, and hands-on cadaveric workshops can reduce complications. Proper case selection, good surgical technique, and better postoperative care are essential for a good outcome in ETV. Although it is difficult to make a preoperative diagnosis of complex hydrocephalus (combination of communicating and obstructive), improving methods to detect the exact type of hydrocephalus before surgery could increase the success rate of ETV and avoid an unnecessary ETV procedure in such cases.
Keywords: complications; endoscopy; intraoperative complication; minimal invasive surgical procedure; neuroendoscopy